Menakar Sejarah Gerakan Radikalisme Islam serta Upaya Pemerintah dalam Mengatasinya - Agil Muhammad Sahal; Agung Bayuseto (FOCUS, 2021)
This article examines the commotion of the Islamic radicalism movement that has sprung up in society, and social media has become a space for new ways to carry out propaganda, recruitment, training, planning, or the doctrine of calling for the establish- ment of an Islamic Khilafah. The government and society have a very important role in maintaining the integrity of this nation, thus, this research focuses on the government’s efforts to eradicate radicalism with plural societies.